Tourism activities in the frontline areas of Sumy region: problems, opportunities and prospects - Olesia Kornus; Natalia Venherska; Mart Reimann; Anatolii Kornus; Viktoriia Patsiuk (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2023)
The Sumy region has great and significant tourism potential. Before the Russo-Ukrainian War, the region had 3,465 historical and cultural monuments, including 367 architectural and urban planning monuments (five of them of national importance). Before the war, the tourism sector was developing steadily, with new types of tourism services and the formation of tourism clusters. However, Russia's Invasion of Ukraine resulted in a significant decrease in tax revenues, which has a negative impact on tourism. The purpose of this paper is to study the peculiarities and future prospects of tourism development in the Sumy region during the war, based on data from a sociological survey conducted in five Ukrainian frontline regions in the framework of the Estonian-Ukrainian research project "Development of Ukrainian frontline communities and tourism business during the war and future strategy", which was supported by the Estonian Research Agency.